Residual baculovirus in insect cell-derived influenza virus-like particle preparations enhances immunogenicity. - Irina Margine; Luis Martinez-Gil; Yi-Ying Chou; Florian Krammer (PLoS ONE)
Influenza virus-like particles are currently evaluated in clinical trials as vaccine candidates for influenza viruses. Most commonly they are produced in baculovirus- or mammalian- expression systems. Here we used different vaccination schemes in order to systematically compare virus-like particle preparations generated in the two systems. Our work shows significant differences in immunogenicity between the two, and indicates superior and broader immune responses induced by the baculovirus-derived constructs. We demonstrate that these differences critically influence protection and survival in a mouse model of influenza virus infection. Finally, we show that the enhanced immunogenicity of the baculovirus-derived virus-like particles is caused by contamination with residual baculovirus which activates the innate immune response at the site of inoculation.